PECULIARITIES OF PROFESSIONAL SKILL FORMATION IN VINNITSA TEACHERS' SEMINARY - Tatiana Zuziak (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
The article reveals the history of the formation of Vinnitsa male seminary in the early 20th century using the archival sources. Educational curriculum and programs of the teachers' seminary have been analyzed, in particular the syllabus of the course «Pedagogy». Peculiarities of the professional skills formation in the seminary are considered. The peculiarities of conducting practical classes for seminary students, which promoted the development of teaching skills in the teaching and education of elementary school students, are analyzed. The acticle characterizes the topics for written works of the course 'Russian language and literature'which aimed at teaching the students consistent and eloquent story-telling, skillful descriptions and logically correct presentation of their arguments. It has been proved that along with theoretical studies and the observation of exemplary teaching in Vinnitsa male seminary, students' practical work in the exemplary school had special significance for the formation of their skills. The great educational effect of the subjects of aesthetic education (compulsory for all pupils) such as singing, graphic arts, music, theory and practice of gardening, handicraft, carpentry and physical education, introduced in the seminary curriculum has been shown. It has been proved that the pupils of Vinnitsa male teaching seminary were best trained for conducting classes in primary schools, they were well-aware of the curriculum and textbooks of the schools and were competent enough about the basic subjects taught in elementary schools. It has been distinguished that a significant feature of Vinnitsa male teacher's seminary was the practical familiriazing students with the educational work of public schools in exemplary schools that operated at the seminary. It has been proved that the graduates of the teachers' seminary were mainly peasants who knew the life of the rural population, its spiritual and material needs well, what, in turn, contributed to the successful formulation of the educational work. The hardship of the material situation of the seminary, the lack of general educational system, and the lack of awareness of the teacher's role in the progress of society by the state officials prevented development of pedagogical education in Podillia.